Role of childhood trauma in addiction: a bibliometric analysis - Kılıç, Kızbes Meral (Journal of Dependence, 2025)
The aim of this study is to examine the trends and study topics in studies on addiction in individuals with childhood trauma between 1993-2025. Bibliometric analysis was performed based on 874 data taken from the Web of Science (WoS) database on February 26, 2025 in this study. Data and graphical presentations were prepared using the Bibliometrix Package in R software and VOSviewer. This study showed that studies on addiction in individuals with childhood trauma have increased over the years. Child Abuse & Neglect was the most productive journal and the United States was the most productive country. In studies conducted on addiction in individuals with childhood trauma, the words most frequently used by authors were abuse, risk, sexual abuse, prevalence, and maltreatment. This study is the first bibliometric study on addiction in individuals with childhood trauma and provides a 32-year perspective. In this study, it was observed that behavioral addictions have also been given importance in recent years and the popularity of terms such as dysregulation, interventions and resilience in the relationship between childhood trauma and addiction has increased over time. As the correlates of childhood trauma emerge, the focus of policy research has shifted to potential protective factors and intervention solutions.